Neurological post-COVID syndrome is associated with substantial impairment of verbal short-term and working memory - Jeyanthan Charles James; Hannah Schulze; Nadine Siems; Christian Prehn; Daniel R. Quast; Nadine Trampe; Ralf Gold; Simon Faissner (Scientific Reports)
Abstract A substantial proportion of patients suffer from Post-COVID Syndrome (PCS) with fatigue and impairment of memory and concentration being the most important symptoms. We here set out to perform in-depth neuropsychological assessment of PCS patients referred to the Neurologic PCS clinic compared to patients without sequelae after COVID-19 (non-PCS) and healthy controls (HC) to decipher the most prevalent cognitive deficits. We included n = 60 PCS patients with neurologic symptoms, n = 15 non-PCS patients and n = 15 healthy controls. Basic socioeconomic data and subjective complaints were recorded. This was followed by a detailed neuropsychological test battery, including assessments of general orientation, motor and cognitive fatigue, screening of depressive and anxiety symptoms, information processing speed, concentration, visuomotor processing speed, attention, verbal short-term and working memory, cognitive flexibility, semantic and phonematic word fluency, as well as verbal and visual memory functions. Neurologic PCS patients had more complaints with significantly higher fatigue scores as well as higher levels of depressive and anxiety symptoms compared to Non-PCS and HC. Deep neuropsychological assessment showed that neurologic PCS patients performed worse in a general screening of cognitive deficits compared to HC. Neurologic PCS patients showed impaired mental flexibility as an executive subfunction, verbal short-term memory, working memory and general reactivity (prolonged reaction time). Multiple regression showed fatigue affected processing speed; depression did not. Self-reported cognitive deficits of patients with neurologic PCS including fatigue, concentration, and memory deficits, are well mirrored in impaired performance of cognitive domains of concentration and working memory. The present results should be considered to optimize treatment algorithms for therapy and rehabilitation programs of PCS patients with neurologic symptoms.